Nostalgia and Archival Footage in Contemporary Hungarian Documentary (Gábor Zsigmond Papp: "The Life of an Agent") - Vincze, Terez (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
Archival and found footage have been playing an important role in Hungarian cinema since the 1960s. Th is type of material has been present not only in documentaries but also in Hungarian feature and experimental films. After a very short summary of the history of the usage of archival footage in Hungarian cinema, I will discuss two contemporary trends in documentaries: the artistic/experimental use and the entertainment-related/nostalgic use of found footage. At the end of the article, I use Gábor Zsigmond Papp’s documentary fi lm The Life of an Agent as an example of the nostalgic use of archival material in the representation of a still-unresolved Hungarian historical problem: socialist secret agents.